2007
DOI: 10.1197/jamia.m2284
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Hybrid Approach to Automated Negation Detection in Clinical Radiology Reports

Abstract: This novel hybrid approach can accurately locate negated concepts in clinical radiology reports not only when in close proximity to, but also at a distance from, negation signals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
72
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(73 citation statements)
references
References 16 publications
1
72
0
Order By: Relevance
“…Syntactic information is also useful to resolve this problem. A hybrid approach by combining regular expression matching with grammatical parsing has been purposed to detect negations [13]. The results showed that the structure grammar rules developed using linguistic principles were more powerful than detecting negated concepts at a fixed distance from negation cues.…”
Section: Introductionmentioning
confidence: 99%
“…Syntactic information is also useful to resolve this problem. A hybrid approach by combining regular expression matching with grammatical parsing has been purposed to detect negations [13]. The results showed that the structure grammar rules developed using linguistic principles were more powerful than detecting negated concepts at a fixed distance from negation cues.…”
Section: Introductionmentioning
confidence: 99%
“…This algorithm has been utilized [26] for finding encounter-based events in clinical electronic medical records and for classifying them. The idea of using syntactic and semantic processing for determining the scope of negation cues has been tackled in many other research studies [27][28][29][30][31][32][33][34].…”
Section: Related Workmentioning
confidence: 99%
“…Previous works have demonstrated the ability to determine positive findings by using NLP to address negation within clinical reports [14][15][16].…”
Section: Introductionmentioning
confidence: 99%